Characterization of Pneumocystis murina Bgl2, an Endo-β-1, 3-Glucanase and Glucanosyltransferase. (18th April 2019) - Kutty, Geetha; Davis, A Sally; Schuck, Kaitlynn; Masterson, Mya; Wang, Honghui; Liu, Yueqin; Kovacs, Joseph A
Abstract: Glucan is the major cell wall component of Pneumocystis cysts. In the current study, we have characterized Pneumocystis Bgl2 (EC 3.2.1.58), an enzyme with glucanosyltransferase and β-1, 3 endoglucanase activity in other fungi. Pneumocystis murina, Pneumocystis carinii, and Pneumocystis jirovecii bgl2 complementary DNA sequences encode proteins of 437, 447, and 408 amino acids, respectively. Recombinant P. murina Bgl2 expressed in COS-1 cells demonstrated β-glucanase activity, as shown by degradation of the cell wall of Pneumocystis cysts. It also cleaved reduced laminaripentaose and transferred oligosaccharides, resulting in polymers of 6 and 7 glucan residues, demonstrating glucanosyltransferase activity. Surprisingly, confocal immunofluorescence analysis of P. murina –infected mouse lung sections using an antibody against recombinant Bgl2 showed that the native protein is localized primarily to the trophic form of Pneumocystis in both untreated mice and mice treated with caspofungin, an antifungal drug that inhibits β-1, 3-glucan synthase. Thus, like other fungi, Bgl2 of Pneumocystis has both endoglucanase and glucanosyltransferase activities. Given that it is expressed primarily in trophic forms, further studies are needed to better understand its role in the biology of Pneumocystis . Abstract : We have demonstrated that Bgl2 of Pneumocystis murina is a β-1, 3 endoglucanase that also has glucanosyltransferase activity. Surprisingly, Bgl2 localized to trophic forms, which lack β-1, 3-glucan, but not to cysts, whose cell wall is composed primarily of β-1, 3-glucan.